Nurturing Heutagogy: Implementing Montessori Philosophy in English Language Acquisition within an Islamic School Context - Jinabe, Megan; Margana, Margana; Sukarno, Sukarno; Sugirin, Sugirin (UIN Salatiga, 2025)
The Montessori method has become a trend in Early Childhood Education, particularly in terms of the students’ language acquisition within the Self-Directed Learning (SDL) framework. While SDL, as proposed in heutagogy, is theoretically ideal for language learning, practical implementations in a faith-based culture are not well understood. Therefore, this research analyses the teaching of the English language in a new educational context: a Montessori classroom in Indonesia that incorporates Islamic principles. Utilizing a qualitative case study approach, this research identifies the synergistic conditions that foster language development and describes the observable pathways of language acquisition within this context. Evidence gathered from classroom observations and teacher interviews identified three pillars that underpin success in this particular classroom environment: (1) radical autonomy, which offers personally meaningful language input; (2) a low anxiety classroom, which encourages spontaneous language production; and (3) a synergistic Islamic classroom environment, which strengthens self-discipline and independence in contrast to the Islamic faith. A specific four-stage sequence of acquisition was identified within this meticulously designed environment. The integration of Islamic character-building with Montessori pedagogy underscores the holistic development of the child and the language itself. This research adds value by addressing pedagogical needs at the cultural level, and, in doing so, establishes a conceptual framework that outlines the stepwise progression of learners within a framework of self-determination.